Bugs! bugs! bugs! - Dussling, Jennifer (New York : DK Pub., 1998)
Describes the hunting activities of various bugs, including the praying mantis, wood ant, and dragonfly.
"Grades 1-3."
Keywords: Predatory insects -- Juvenile literature; Insects